God Spatially Above and Spatially Extended: The Rationality of Ibn Taymiyya’s Refutation of Faḫr al-Dīn al-Rāzī’s Ašʿarī Incorporealism - Hoover, Jon (Arabica, 2022)
Ibn Taymiyya (d. 728/1328) wrote his tome Bayān talbīs al-ǧahmiyya to refute Ašʿarī kalām theologian Faḫr al-Dīn al-Rāzī’s (d. 606/1210) argument in Taʾsīs al-taqdīs that God is not corporeal, located, or spatially extended. Bayān talbīs al-ǧahmiyya is the largest known refutation of kalām incorporealism in the Islamic tradition, and al-Rāzī’s Taʾsīs al-taqdīs was apparently the most sophisticated work of its kind circulating in Ibn Taymiyya’s Mamlūk scholarly milieu. Ibn Taymiyya in Bayān talbīs al-ǧahmiyya deconstructs al-Rāzī’s rational arguments and explicates an alternative theology of God’s relation to space. Translating his understanding of the meaning of the Qurʾān and the Sunna into kalām terminology and drawing on Ibn Rušd’s (d. 595/1198) Aristotelian notion of place as the inner surface of the containing body, Ibn Taymiyya envisions God in Bayān talbīs al-ǧahmiyya as a very large indivisible and spatially extended existent that is above and surrounds the created world in a spatial sense.